PENYALAHGUNAAN NAPZA DI INDONESIA: Pendekatan Kajian Keislaman dan Perspektif Pekerjaan Sosial - Lukman Prasetyo Utomo (KOMUNITAS, 2017)
Drug Abuse in the world consistently increases where almost 12% (15.5 million people up to 36.6 million people) of users are heavy addicts. According to the World Drug Report of 2012, the productions of drugs increased, one of which was opium production. It increased from 4,700 tons in 2010 to 7,000 tons in 2011. Drug abuse in Indonesia also increased from year to year proven according to BNN survey results with UI and other universities that in 2005 the prevalence percentage was 1.7% in Indonesia, in 2008 prevalence percentage was 1.99%, in 2012 prevalence percentage was 2.2%. Furthermore, the number of drug use according to Head of BNN actually increased significantly in the period of June to November 2015 that is 1.7 million people. In June 2015 the number of users was 4.2 million and in November 2015 the number of users was 5.9 million. Today the problem of drug abuse already becomes a national disaster. Drug abuse has been the concern of all people for several reasons; first, the use of drugs by various societies has been in critical condition. Second, the impacts are not only generated to the users but also damage the people’s lives and nation’s life. Thirdly, Indonesia is not only a consumer country but a producer country as well, so the Indonesian government firmly declares that Indonesia is Drug emergency or declares war on Drugs. The impact of drug abuse is very complex starting from victims, families, peer victims, until the community. So the view of Islam associated with the abuse of these drugs is that drugs are goods which damage the mind, memory, heart, soul, mental and physical health such as khomar. Therefore, drugs are also included in the category which is forbidden by Allah SWT and the scholars agree that drugs are illicit when people are not in an emergency situation. As a helping profession, social work has a fundamental mission to solve social problem whether it is a problem experienced by individuals, families, groups, or communities. In its development, social workers reflect relief efforts to vulnerable groups. Drug addicts are one part of Indonesian societies who has equal position, rights, obligations and roles with other Indonesian societies in all aspects of life and the life which in essence still has potential that can be developed through a special program, namely the social welfare effort program for the addicts of Drugs with social rehabilitation. Here social workers play a role in helping / assisting the recovery of victims in realizing their social function.